Dangerous Liaisons: Working Women and Sexual Justice in the American Civil War - E. Susan Barber; Charles F. Ritter (European Journal of American Studies)
The American Civil War drew thousands of white and black women into paid and unpaid work for the Union and Confederate armies.  While the armies provided some women with a reliable income, their very proximity also represented a dangerous liaison that drew them into closer contact with Union troops that rendered them vulnerable to sexual assault.  By 1865, more than four hundred Union soldiers had been court-martialed for sexual crimes against white and black women and girls. At the war’s onset, the Union’s judge advocate corps, which tried soldiers for violations of the articles of war, was ill-prepared to adjudicate sexual crimes. By the war’s end, however, an ethic of sexual justice emerged from Union military courts to provide women with a means of redressing their wartime sexual violation.